Implementation Strategy for Religious Moderation of Islamic Religious Education Students in the Digital Era: Tantangan Mahasiswa Pendidikan Agama Islam Dalam Mengimplementasikan Moderasi Beragama Di Era Digital - Muhammad Iqbal Jamaludin; Hafidz Imaduddin; Mohammad Asrori (STAI Terpadu Yogyakarta, 2025)
This study aims to explore how strategy Islamic Religious Education (PAI) students implement religious moderation in the digital era. The development of technology marked by digitalization is of course very significant in various aspects of life, including Islamic religious education. This makes religion and technology go hand in hand. The presence of religious moderation is an important foundation in dealing with information and various views spread in digital media. This information is often unfiltered and tends to be provocative. This research was conducted with a literature study that involved collecting information through books, scientific articles, and other internet literature. The results showed that PAI students in implementing religious moderation in the digital era are instilling religious moderation values and fortifying against extremism. Efforts that can be made by PAI students in implementing religious moderation in the digital era are by campaigning for religious moderation through social media, creating digital content that is attractive to internet users and creating online seminars, and instilling religious and cultural values based on moderation.